(untitled) (Applied Biological Research, 2017)
Field studies were conducted to evaluate the efficacy of six insecticides against white grub, Lepidiota mansueta, in potato in 2012 and 2013 at Majuli river island in Assam (India). All the insecticide treatments significantly reduced tuber damage as against untreated control. Of the insecticides tested, fipronil 5 SC @ 150 g a.i. ha-1 showed low tuber damage on weight basis (5.24 and 4.57%) and was at par with fipronil 5 SC @ 100 g a.i. ha-1 (5.91 and 5.09%), chlorpyriphos 20 EC @ 400 g a.i. ha-1 (5.55 and 6.2%) and quinalphos 25 EC @ 400 g a.i. ha-1 (6.14 and 6.72%). On number basis, fipronil 5 SC @ 150 g a.i. ha-1 showed lowest tuber damage (4.2%), followed by chlorpyriphos 20 EC @ 400 g a.i. ha-1 (5.25%) and quinalphos 25 EC @ 400 g a.i. ha-1 (5.66%). All insecticide treatments were at par in tuber yield, except emamectin benzoate 5% SG @ 12.5 g a.i. ha-1. Highest cost benefit ratio was observed in chlor pyriphos 20 EC @ 400 g a.i. ha-1 treatment (2.50 and 2.62), followed by quinalphos 25 EC @ 400 g a.i. ha-1 (2.23 and 1.85). Chlorpyriphos 20 EC @ 400 g a.i. ha-1 and quinalphos 25 EC @ 400 g a.i. ha-1 seem better alternatives than fipronil to reduce infestation of L. mansueta in potato.